Placental Cryoextract Corrects the Level of Thyroid Hormones in Rats - Malova , Natalia; Komarova, Irina; Sirotenko, Larisa; Brechka, Natalia; Kurilko , Yuliya; Komisova , Tatiana; Goltsev , Anatoliy (Problems of Cryobiology and Cryomedicine, 2021)
Effectiveness of cryopreserved placental drug ‘Placental cryoextract’ to correct the reproductive system disorders, occurring against the background of low levels of thyroid hormones, was studied in 50 male rats with mercazolyl hypothyroidism. Using standard test systems for animals, the level of total and free forms of thyroid hormones, total testosterone and estradiol was determined. The morphofunctional state of sperm (number, motility, pathological forms) was traditionally assessed. It was shown that the introduction of the biological product (at a dose of 50–150 μl / kg) restored the functional activity of the thyroid gland of animals, and the lowest dose was more effective. Placental cryoextract also had a dose-dependent effect on the reproductive system of animals with hypothyroidism: the most effective dose was 150 μl / kg, which maximally restored the morphofunctional parameters of sperm and stimulated testosterone production as well as normalized the Ts / E2 ratio. Cryopreserved placenta extract can be considered as a potential drug for the correction of hypothyroidism and reproductive disorders of endocrine origin in male rats. Probl Cryobiol Cryomed 2021; 31(4): 353–363